The Ultimate Christmas collection - Big Idea Productions ([Franklin, TN?] : Big Idea, 2012)
A set of six Christmas films and music CD. Toy that saved Christmas: The children of Dinkletown are convinced they need more toys until a toy teaches them that Christmas is about giving, not getting. Star of Christmas: In 1880s London, two producers of a Christmas musical are worried when a church down the street puts on a pageant featuring a priceless artifact. Saint Nicholas: Bob tells a story of a little boy named Nicholas who made a discovery in Bethlehem that changed Christmas forever. Christmas sing-along songs: A holiday sing-along of VeggieTales favorites hosted by Bob and Larry. It's a meaningful life: Faced with losing his father's toy factory to a greedy business mogul, Stewart discovers a ticket for a special one-night-only train ride with a mysterious conductor to visit his past, present, and future. Little drummer boy: Junior Asparagus stars as The Little Drummer Boy, a lonely child who finds the true meaning of Christmas when he stumbles upon the birth of the baby Jesus.
v. 1. Toy that saved Christmas -- Star of Christmas -- Saint Nicholas (ca. 120 min.). v. 2. Christmas sing-along songs! -- It's a meaningful life -- Little drummer boy (ca. 123 min.). CD. 25 favorite Christmas songs!
DVD, region 1, NTSC, widescreen.
Subtitled for the deaf and hard of hearing.
Dan Anderson, Mike Nawrocki, Matthew Hodge, Tim Hodge, Jim Poole, Jacquelyn Ritz, Mike Sago, Lisa Vischer, Phil Vischer, Shelby Vischer.
Toy that saved Christmas: written by Phil Vischer ; directed by Phil Vischer and Chris Olsen ; produced by Chris Olsen. Star of Christmas: produced by David Pitts ; directed by Tim Hodge ; written by Phil Vischer. Saint Nicholas: Music, Kurt Heiseche ; writers, Robert Lee, Mike Nawrocki, Phil Vischer. Christmas sing-along songs: It's a meaningful life: directed by Brian K. Roberts ; written by Mark and Mike Nawrocki ; produced by Leslie Ferrell and Brian K. Roberts. Little drummer boy: directed by Brian K. Roberts ; produced by David Pitts ; written by Mike Nawrocki and Mark Steele.
Title from web.
Rating: Not rated.
Keywords: Generosity -- Juvenile films; Christian life -- Juvenile films; Christmas plays -- Juvenile films; Pageants -- Juvenile films; Antiquities -- Juvenile films; Musicals -- Juvenile films; Nicholas, -- Saint, Bishop of Myra -- Juvenile films; Santa Claus -- (Fictitious character) -- Juvenile films; Time travel -- Juvenile films; Contentment -- Juvenile films; Drummers (Musicians) -- Juvenile films; Video recordings for the hearing impaired; Children's television programs; Christmas television programs; Animated television programs; Video recordings for the hearing impaired